Perlindungan Hukum Terhadap Pura Sebagai Kawasan Suci Dari Komersialisasi Budaya Untuk Pariwisata - Ida Bhujangga Putri Vaisnava; I Wayan Rideng; Diah Gayatri Sudibya (Jurnal Analogi Hukum, 2024)
The presence of tourism brings a new paradigm. To raise legal issues, so far the temple in this case as a holy place is often commercialized even though the temple itself is a sacred area for Hindus. How is the Regulation of the Temple as a sacred area from Commercialization of Culture for Tourism? and How is the Form of Legal Protection of the Temple as a sacred area from Commercialization of Culture for Tourism?, This research uses normative research. As a result, the form of legal protection of the temple as a sacred area from the commercialization of culture for tourism in Bali is in the form of prohibition of commercialization, setting limits and supervision, as well as the establishment of law enforcement and enforcement of sanctions in the form of formal law and the application of customary sanctions.